Tophi: A pointer towards the diagnosis of gout - Jency Maria Koshy; Mary John; Rupinder Kaur; Lydia Solomon (Wolters Kluwer Medknow Publications, 2014)
Tophi are deposits of monosodium crystals in people with long-standing gout. We report a case of a 34-year-old male presenting with joint pains and soft yellowish swelling over the web spaces of the toes. Aspiration of the same revealed monosodium crystals leading to a diagnosis of Tophaceous gout.